A Comprehensive Description of the Anatomy and Histochemistry of Psychotria capillacea (Müll. Arg.) Standl. and an Investigation into Its Anti-Inflammatory Effects in Mice and Role in Scopolamine-Induced Memory Impairment - Anelise Samara Nazari Formagio; Wagner Vilegas; Cândida Aparecida Leite Kassuya; Valter Paes De Almeida; Jane Manfron; Elisabete Castelon Konkiewitz; Edward Benjamin Ziff; Janaine Alberto Marangoni Faoro; Jessica Maurino Dos Santos; Ana Julia Cecatto; Maria Helena Sarragiotto; Rosilda Mara Mussury (MDPI AG, 2024)
Species of the genus Psychotria are used in popular medicine for pain, inflammatory symptoms, and mental disorders. Psychotria capillacea (Müll. Arg.) Standl. (Rubiaceae) is commonly known as coffee and some scientific studies have demonstrated its therapeutic potential. The goal of this study was to investigate the anti-inflammatory and neuroprotective effects, and acetylcholinesterase (AChE) inhibitory activity of a methanolic extract obtained from leaves of P. capillacea (MEPC), as well as the micromorphology and histochemistry of the leaves and stems of this plant. In addition, the MEPC was analyzed by UHPLC-MS/MS and the alkaloidal fraction (AF) obtained from the MEPC was tested in a mouse model of inflammation. MEPC contained three indole alkaloids, one sesquiterpene (megastigmane-type) and two terpene lactones. MEPC (3, 30 and 100 mg/kg) and AF (3 and 30 mg/kg) were evaluated in inflammation models and significantly inhibited edema at 2 h and 4 h, mechanical hyperalgesia after 4 h and the response to cold 3 h and 4 h after carrageenan injection. Scopolamine significantly increased the escape latency, and reduced the swimming time and number of crossings in the target quadrant and distance, while MEPC (3, 30 and 100 mg/kg), due to its neuroprotective actions, reversed these effects. AChE activity was significantly decreased in the cerebral cortex (52 ± 3%) and hippocampus (60 ± 3%), after MEPC administration. Moreover, micromorphological and histochemical information was presented, to aid in species identification and quality control of P. capillacea. The results of this study demonstrated that P. capillacea is an anti-inflammatory and antihyperalgesic agent that can treat acute disease and enhance memory functions in mouse models.